The Effect of Subject-Teacher Meeting Activities on The Teacher’s Teaching Quality and Student’s Learning Outcomes - Samsudin; Wiyono, Bambang Budi; Putra, Arda Purnama; Maisyaroh; Musa, Khalip (Migration Letters, 2023)
One of the efforts conducted to improve the quality of education in Indonesia is improving the teacher’s teaching quality. If the teacher can manage the learning process effectively, it will be easy to facilitate the student learning process effectively as well. One program that can be carried out is through the subject-teacher meeting (STM). However, so far, there has not been much study on how the implementation of subject-teacher meetings affects the teacher’s quality of learning. This study aimed at examining the effect of STM on teachers’ teaching quality and students’ learning outcomes. This research was conducted in East Java Indonesia with a total sample of 112 teachers using the cluster random sampling technique. Data collection techniques employed questionnaires and documentation, while data analysis techniques used descriptive statistics and structural equation modeling. The results showed that STM activities had a direct effect on the teacher’s teaching quality, and they had direct and indirect effects on students’ learning outcomes. Some of the effective activities are preparing a learning implementation plan that also has a direct effect on students’ learning outcomes. The teacher’s teaching quality has a direct effect on student learning outcomes. The higher the teacher’s teaching quality, the higher the learning outcomes achieved by the students.